Kontribusi Pajak Bumi Dan Bangunan (PBB-P2) Terhadap Pendapatan Asli Daerah Kabupaten Sidoarjo Tahun 2023 - Putri Ayu Widya Kusuma; Riska Ayu Lestari; Revienda Anita Fitrie; Eva Hany Fanida (Jurnal Ilmiah Aset, 2026)
This study aims to analyze the effectiveness and contribution of Rural and Urban Land and Building Tax (PBB-P2) to the Regional Original Income (PAD) of Sidoarjo Regency in 2023. The study uses a qualitative approach with a literature study method, where data is obtained from scientific journals, reports from the Regional Tax Service Agency (BPPD) of Sidoarjo Regency, APBD documents, and various relevant library sources. The results show that the realization of PBB-P2 revenue in Sidoarjo Regency in 2023 reached IDR 292 billion from a total PAD of IDR 1,851.09 billion, with a contribution rate of 15.77% to total PAD and 24.20% to total regional taxes. In terms of its effectiveness, PBB-P2 revenue during the 2020–2023 period reached an average of 106.3%, which is categorized as very effective. However, the contribution of PBB-P2 to PAD is still not optimal due to several factors, including low taxpayer compliance, limited collection administration capacity, and outdated tax object data. Therefore, efforts are needed to focus on quality and quantity or tax expansion, update the NJOP database, and develop digital services to strengthen regional fiscal independence.